An Implemantation of Case Grammar in Teaching English Vocabullary - Habib Syukri Nst (Journal on Education, 2022)
This article discusses about Case Grammar that had applied in linguistics development. This grammar was very useful for the linguistics development to supported the linguistics theory especially for the syntactic development. Case Grammar is a system of linguistic analysis, focusing on the link between the valence of a verb and the grammatical context it requires, created by the American linguist Charles J. Fillmore in (1968). Fillmore published his theory of Case grammar, which highlighted the fact that syntactic structure can be predicted by semantic participants. It focuses on the link between the number of subjects, objects, and so on of a verb and the grammatical context it requires. However, people have realized that some research findings of case grammar can indeed be applied in foreign language teaching, vocabulary teaching is in the case. This article will briefly introduce what case grammar is and its application in vocabulary teaching.